2012
DOI: 10.1159/000338623
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Intravitreal Ranibizumab and Laser Photocoagulation for Aggressive Posterior Retinopathy of Prematurity

Abstract: Purpose: To report on 2 cases of aggressive posterior retinopathy of prematurity (ROP) treated with intravitreal ranibizumab (Lucentis®) and laser photocoagulation. Methods: Two premature females, born at 25 and 26 weeks’ gestation with a birth weight of 530 and 550 g, respectively, with aggressive posterior ROP received combined treatment with laser photocoagulation and intravitreal ranibizumab (0.3 mg [30 µl]) to each eye. Structural outcomes were evaluated by indirect ophthalmoscopy and documented by retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 14 publications
1
24
0
2
Order By: Relevance
“…The aim of laser photocoagulation is to decrease VEGF levels produced by the avascular retina by ablating the retinal periphery. Lately, anti-VEGF drugs have been used as monotherapy agents or in addition to laser photocoagulation, with successful results obtained (7)(8)(9)(11)(12)(13)(14)(15)(16) . The majority of studies have reported the results of bevacizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of laser photocoagulation is to decrease VEGF levels produced by the avascular retina by ablating the retinal periphery. Lately, anti-VEGF drugs have been used as monotherapy agents or in addition to laser photocoagulation, with successful results obtained (7)(8)(9)(11)(12)(13)(14)(15)(16) . The majority of studies have reported the results of bevacizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have reported the results of bevacizumab therapy. There are a few case series presenting results with ranibizumab (7,8) . Although there are stu dies comparing the efficacy of ranibizumab and bevacizumab in patients with age-related macular degeneration, to the best of our knowledge, the present study is the first to compare their efficacy in patients with ROP (17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jang et al, (21) reportaron un paciente con ROP estadio 3 en zona I bilateral que fue tratado con termoterapia transpupilar láser más ranibizumab, con regresión completa 3 meses después del tratamiento pero con desprendimiento de retina bilateral después de este tiempo. Honda et al, informaron en un paciente contracción aguda de la membrana proliferativa que dio lugar a desprendimiento de retina en forma de embudo después de bevacizumab intravítreo para ROP etapa 4A (22), lo que indica la importancia del seguimiento estrecho (23).…”
Section: Discussionunclassified
“…The use of anti-vascular endothelial growth factor (anti-VEGF) agents is a current treatment option for ROP. Bevacizumab (Avastin; Genentech Inc., San Francisco, Calif., USA) and ranibizumab (Lucentis; Genentech Inc.) are two anti-VEGF agents with different molecular sizes, structures, and half-lives, and both of them have shown efficacy in the treatment of ROP [3,4,5,6]. However, preterm babies have incomplete retinal vascular development and areas of peripheral avascular retina.…”
Section: Introductionmentioning
confidence: 99%